Array-CGH increased the diagnostic rate of developmental delay or intellectual disability in Taiwan - Chung-Lin Lee; Chen-Hao Lee; Chih-Kuang Chuang; Huei-Ching Chiu; Yen-Jiun Chen; Chao-Ling Chou; Peih-Shan Wu; Chih-Ping Chen; Hsiang-Yu Lin; Shuan-Pei Lin (Elsevier, 2019)
Background: Unexplained developmental delay or intellectual disability (DD/ID) has an estimated prevalence of about 3%-5% in the general population of Taiwan. Array comparative genomic hybridization (array-CGH) is a high-resolution tool that can detect about 50 Kb chromosome aberrations. A previous study has reported a detection rate of 10%-20% for this array.1 This study aimed to investigate and compare the diagnosis rate for DD/ID using array-CGH and conventional chromosome study in DD/ID patients in Taiwan. Methods: We enrolled 177 patients with DD/ID who underwent array-CGH examination at the MacKay Memory Hospital between June 2010 and September 2017. The copy number variants (CNV) were classified into the following three groups: pathogenic (potential pathologic variant), benign (normal genomic variant), and uncertain clinical significance (variance of uncertain significance, VOUS), according to the ACMG guideline.2 Results: Of the 177 enrolled patients, 100 (56.5%) were men and 77 (43.5%) were women. Ages ranged from 3 months to 50 years, with a median age of 5.2 years. Total 32.0% (32/100) male patients had pathogenic CNV, and 32.5% (25/77) female patients had pathogenic CNV. The ratio of pathogenic CNV in male and female patients was not significantly different (p = 0.379). The proportions of pathogenic CNV at <3 years, 3-6 years, 6-12 years, 12-18 years, and >18 years of age were 32.3% (31/96), 19.4% (6/31), 34.8% (8/23), 16.7% (2/12), and 66.7% (10/15), respectively. The overall diagnosed rate of DD/ID with pathogenic CNV was 27.7% (49/177) using array-CGH in this study. There were 105 patients with conventional karyotyping and array-CGH data at the same time. Nineteen (18.1%) patients had visible chromosomal abnormality. Total 32/105 (30.5%) patients could find at least one pathogenic CNVs. The array-CGH had a higher diagnosed rate than the conventional karyotyping in clinical application. Conclusions: Although array-CGH could not detect point mutation, balanced translocations, inversions, or low-level mosaicism, the diagnosis rate in clinical application was up to 46.3% and 2.5 times that of conventional karyotyping analysis (18.1%). This study demonstrated that array-CGH is a powerful diagnostic tool and should be the first genetic test instead of conventional karyotyping analysis for patients with unexplained DD/ID. Key Words: array-CGH, chromosomal microarray, developmental delay, intellectual disabilities, Taiwan